Analisis Yuridis Terhadap Peranan Notaris dalam Pembuatan Perjanjian Perkawinan Untuk Mewujudkan Kepastian Hukum (Studi Kasus Kantor Notaris Hendy Bkry Agustino Kota Tanjung Pinang) - Gotama, Robi; Respationo, Soerya; Tartib, M.; Erniyanti, Erniyanti; Nofrial, Ramon (Universitas Ekasakti, 2023)
This thesis aims to conduct a juridical analysis of the role of notaries in the creation of prenuptial agreements with the objective of ensuring legal certainty within the context of marriage law in Indonesia. This research encompasses a comprehensive examination of the legal regulations governing the role of notaries in the creation of prenuptial agreements, the implementation of notarial practices in the prenuptial agreement process, and the identification of factors that may hinder the attainment of legal certainty. Through a normative legal approach, this thesis analyzes various legal provisions, regulations, and notarial guidelines pertaining to prenuptial agreements. Additionally, this research involves interviews with notaries practicing in this field to gain a deeper understanding of the implementation of the notarial role and the challenges faced in ensuring legal certainty. The findings of this research are expected to provide a more profound insight into the role of notaries in prenuptial agreements and their contribution to legal certainty within the context of marriage law in Indonesia. Furthermore, this study may serve as a foundation for improvements or refinements in legal regulations and notarial practices, aimed at enhancing legal certainty for individuals planning to marry or already married in Indonesia. By combining normative and empirical legal approaches, this thesis seeks to provide a comprehensive picture of the role of notaries in creating legal certainty in marriage agreements.